Total Phenolic Content, Biomass Composition, and Antioxidant Activity of Selected Marine Microalgal Species with Potential as Aquaculture Feed - Vasilis Andriopoulos; Maria D. Gkioni; Eleni Koutra; Savvas G. Mastropetros; Fotini N. Lamari; Sophia Hatziantoniou; Michael Kornaros (MDPI AG, 2022)
There has been growing interest in microalgal biomolecules for health and cosmetics, as well as in the use of microalgae as aquaculture feed due to the need to replace fishmeal and fish oil with sustainable yet equally nutritious alternatives. Aim of this study is to evaluate the potential of five marine microalgal species, namely Chlorella minutissima, Dunaliella salina, Isochrysis galbana, Nannochloropsis oculata and Tisochrysis lutea, for the co-production of antioxidants and aquaculture feed. Batch cultivation was performed under saturating light intensity and continuous aeration. Freeze-dried biomass was extracted sequentially with water and methanol and evaluated for phenolic content and antioxidant activity, as well as proximate composition and fatty acid profile. Methanolic extracts of C. minutissima presented the highest phenolic content, measured with the Folin-Ciocalteu assay, and antioxidant activity. However, HPLC and LC-MS showed the presence of non-pigment compounds only in T. lutea. Total phenolic content and antioxidant activity were correlated to chlorophyll content. N. oculata and T. lutea were rich in eicosapentaenoic acid and docosahexaenoic acid, respectively, as well as in protein. In conclusion, N. oculata and T. lutea are suitable candidates for further optimization, while the data presented suggest that pigment effects on the Folin-Ciocalteu method require reconsideration.